Protoplanetary Formation of Earth: Explanation of Magnesium, Calcium, and Aluminum Enrichment in the Upper Mantle and Crust and in the Moon and the Retention of Primordial Water - Herndon, J. Marvin (European Journal of Applied Sciences, 2025)
In 1944 Arnold Eucken showed that the first primordial condensate from a cooling gas of solar composition at high-pressures, high temperatures would be molten iron, followed at lower temperatures by silicate minerals, and at still lower temperatures, by ices and gases. I validated the protoplanetary origin of Earth in the following ways: 1) By thermodynamic considerations I connected high-pressure, high-temperature primordial condensation with the oxidation state and minerals of the enstatite chondrites and; 2) By ratios of mass I connected the minerals of the Abee enstatite chondrite to the components of Earth’s interior. According to Eucken’s paradigm, at high-pressures, high-temperatures iron metal first condenses as a liquid followed by mantle silicates. However, at the next step of his paradigm, following lower mantle condensation, there appears to be no thermodynamically feasible way to account for the “excess” elements, magnesium, calcium, and aluminum remaining in the gas phase (for subsequent condensation), at least none I have been able to ascertain in decades of investigation. Here, I propose an Eucken paradigm shift, provide petrologic evidence for it, and briefly discuss concomitant implications on planetary and lunar formation, and planetary retention of primordial water resources with focus on the formation of Earth’s oceans. According to the Eucken paradigm, molten iron first condenses, followed by condensation of the lower mantle silicates. I propose instead that virtually all of the elements of the endo-Earth (lower mantle plus core) are contained in that first liquid condensate, defined as endo-E condensate. Such a circumstance would provide a means for incorporating primordial water into mantle silicates and leave the three “excess” elements, magnesium, calcium, and aluminum in the gas phase to condense later as part of the matter that formed the outer portion of Earth and the Moon.